1996
DOI: 10.1063/1.471032
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated desorption of neutral CF3 from CF3I on Ag(111)

Abstract: The low temperature thermal chemistry of CF3I on Ag (111) presents an example of competing reaction pathways; molecular desorption vs desorption of radical CF3. Temperature programmed desorption and angle resolved temperature programmed desorption, complemented with Auger electron spectroscopy and low energy electron diffraction, were used to discern the mechanism of the CF3 radical desorption channel. CF3 desorption is limited to the first monolayer of CF3I; 0.75 ML CF3I is the coverage used for angular depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In our TPR/D survey, consistent with the work of White and co-workers, ,, we found that the thermal chemistry of CF 3 I adsorbed on Ag(111) involves molecular desorption below150 K and the dissociation of the C−I bond to form CF 3(ad) and I (ad) . There is no C−F bond cleavage upon further heating.…”
Section: Results and Interpretationsupporting
confidence: 88%
“…In our TPR/D survey, consistent with the work of White and co-workers, ,, we found that the thermal chemistry of CF 3 I adsorbed on Ag(111) involves molecular desorption below150 K and the dissociation of the C−I bond to form CF 3(ad) and I (ad) . There is no C−F bond cleavage upon further heating.…”
Section: Results and Interpretationsupporting
confidence: 88%
“…Following the adsorption of 0.2L (1L = 10 -6 Torr s) CF 3 I at 180 K, we found CF 3 radical ejection (monitored as CF 2 + , m / e = 50, which is the most abundant fragment of the CF 3 radical in the mass spectrometer 8 ) near 320 K, as indicated in the TPR spectra of Figure A. In agreement with White, our observations confirm that CF 3 I thermally dissociates at a submonolayer coverage on Ag(111) to form CF 3(ad) and I (ad) . The decomposition channel is limited to C−I bond scission, and there is no evidence for C−C bond formation on this surface.…”
supporting
confidence: 87%
“…In this paper, we present evidence for the insertion reaction of methylene on the Ag(111) surface, which is based on the interaction between methylene and trifluoromethyl groups coadsorbed on this surface. Methylene was generated on the surface by thermal disruption of the C−I bonds in adsorbed methylene iodide (CH 2 I 2 ) at or below 200 K. CH 2 I 2 has been demonstrated as a source of adsorbed methylene on a variety of metal surfaces by several research groups. Similarly, as reported by White et al, the surface-bound trifluoromethyl was prepared by the cleavage of the C−I bond in the chemisorbed trifluoromethyl iodide (CF 3 I) well below 200 K.…”
mentioning
confidence: 89%
“…Desorption of CF 4 has been reported in the reactions of CF 3 I on Ni(111) 12 and Ru(001). 13,14 CF 3 radical desorption has been observed during the reaction of CF 3 I on Ag(111), [15][16][17] Ni(100), 18,19 Ni(111), 12 Pt(111), 20 and Ru-(001). 13 CF 2 fragments desorb during temperature-programmed desorption of CF 3 I on Pt(111), 20 Ni(111), 12 and Ru(001).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the reactions on Mo(110) we will describe here, reactions of CF 3 I on other metal surfaces yield gaseous reaction products containing at least one C−F bond, the strongest single bond that carbon forms. Desorption of CF 4 has been reported in the reactions of CF 3 I on Ni(111) and Ru(001). , CF 3 radical desorption has been observed during the reaction of CF 3 I on Ag(111), Ni(100), , Ni(111), Pt(111), and Ru(001) . CF 2 fragments desorb during temperature-programmed desorption of CF 3 I on Pt(111), Ni(111), and Ru(001). , Following adsorption of CF 3 I on Cu(111), cleavage of a single C−F bond in adsorbed CF 3 results in the selective formation of adsorbed CF 2 moieties whose subsequent coupling yields gaseous C 2 F 4 …”
Section: Introductionmentioning
confidence: 99%